Program Pengalaman Lapangan Mahasiswa Dalam Pengembangan Media Pembelajaran Kreatif Di SMA Negeri 4 Pematangsiantar - Octavia Selpi Sihotang; Rick Hunter Simanungkalit; Bahtera Rams Saputra Siahaan; Clara Theresia Lumbantoruan; Mediana Lorenza Br Tumorang; Deta Friska Amelia Marbun; Rosanti Samosir (Getpress Management Journals, 2025)
The Field Experience Program (PPL) serves as a strategic platform for pre-service education students to apply their pedagogical, professional, social, and personality competencies in real school settings. One of the important contributions of PPL students is the development of creative learning media that can support the teaching-learning process to make it more effective, engaging, and contextual. This study aims to describe the contributions of PPL students to the development of creative learning media at SMA Negeri 4 Pematangsiantar, as well as the implementation of the developed media and its impact on the teaching-learning process. This research employs a concrete experience approach with a qualitative method. The research subjects include PPL students, mentor teachers, and students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was performed through stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that PPL students actively contribute to developing various creative learning media, both digital and non-digital based, such as interactive presentation media, instructional videos, and creative worksheets. These media help increase student engagement, facilitate understanding of the material, and support the creation of more innovative learning. Thus, the presence of PPL students provides a positive contribution to the development of creative learning media at SMA Negeri 4 Pematangsiantar.